Methodological Considerations for Development of Research Support Systems. (1st September 2016) - Holmberg, Stig C.; Håkansson, Anita M.
Abstract : The article introduces the development of research support systems (RSS) as a special form of information systems (IS) development. Building on experiences from a concrete case several crucial differences between RSS development and development of conventional business support systems (BSS) are identified. So, development for RSS means less of mission and more of continues collaboration, less of producing and more of reciprocal learning and social change. It also involves an expanded universe of discourse that requires support more from an IS researcher and less of a conventional IS-developer. Further, there are issues of ethics and funding that makes RSS development extra challenging. All this represents a shift in focus away from How to do things, toward, What things to do. The article is closed with some tentative guidelines for RSS development. Those include preparing, learning, working arena, anticipatory acting, prototyping and stepwise improvement and scrutiny.